Avaliação histológica, ultraestrutural e molecular de córneas com ceratocone e dos efeitos do crosslinking rápido sobre os ceratócitos cultivados em modelo 3D - Covre, Joyce Luciana [UNIFESP] (2021)
Purpose: Characterize healthy and keratoconus human corneas and keratocytes using histochemical, ultrastructural and molecular analysis and to evaluate the effects of crosslinking treatment at different times on healthy and KC keratocytes cultured in the 3D model. Methods: Cornea samples from control and KC patients were collected and processed for histological, biochemical, immunohistochemical and ultrastructural analyses. Primary keratocytes from control and KC corneas were isolated by collagenase digestion and cultured in DMEM/Ham\'s F12 medium supplemented with 2 % fetal bovine serum. After these cells reach the confluence state (~30 days), they were processed for Western blot analysis to evaluate protein levels implicated in cell structure, adhesion and signaling and an analysis of the lipid profile was performed. Cultured keratocytes were also subjected to CXL treatment at different times. After 24 hours viable cells were quantified by MTT and LDH techniques and apoptotic cells were counted using the caspase 3 marker. The levels of pro-inflammatory cytokines IL-6 and IL-8 and MMP-3, MMP-9 from the supernatants were tested by an enzymelinked immunosorbent assay (ELISA). Results: Histological analysis showed that stroma from KC corneas presented disorganized collagen fibers compared to control samples. Picrosirius-polarization analysis demonstrated enhanced birefringence of collagen networks from control corneas compared to KC. Densitometry of yellow-red/ green birefringence of collagen fibers confirmed these findings and indicates a loss of collagen alignment in the KC. Ultrastructural analysis of KC cornea demonstrated loose fibrillar networks of stroma with small and thin collagen fibril diameters compared to the control samples. In addition, cultured KC cells showed reduced levels of vimentin, focal adhesion kinase (FAK), β1-integrin, keratocan and the activation of Src tyrosine. By contrast, lumican levels were increased in the KC cells and in the corneal stroma. In the analysis of the lipid profile, the potential biomarkers were shown to be completely different in cells with keratoconus compared to control cells (normal). After 24 hours of treatment with CXL, cell viability assessed by MTT and LDH assays indicated that there were no significant changes in the healthy and keratoconus groups. On the other hand, the immunofluorescence analysis showed increased levels of caspase 3 cleaved in healthy cells and keratoconus after 24 hours of treatment with CXL for 30 minutes. The quantification of the levels of pro-inflammatory cytokines IL- 8 and IL-6 and MMP-3 and -9 did not change. Conclusion: Our findings provide that KC is associated with a marked alteration of structural and molecular patterns of corneal stroma and keratocytes. This may be of significance for explanation of pathogenesis of corneal ectactic diseases.